A cross-sectional quantitative analysis of the natural history of Farber disease: an ultra-orphan condition with rheumatologic and neurological cardinal disease features - Zielonka, Matthias; Garbade, Sven; Kölker, Stefan; Hoffmann, Georg F.; Ries, Markus (Genetics in medicine, 2018)
PurposeFarber disease (OMIM 22800) is an ultrarare progressive multisystemic neurodevelopmental storage disorder caused by a deficiency of the lysosomal enzyme acid ceramidase (AC). Hard clinical end points for future clinical trials remain to be defined.MethodsWe quantitatively analyzed published cases with Farber disease (N = 96). The main outcome variables were survival and diagnostic delay. As a potential predictor of survival, the influence of residual AC enzyme activity was investigated. The analysis was performed in compliance with STROBE criteria.ResultsThe median survival period of the study population was 3 years. The median age at disease onset was 3 months, and the median age at diagnosis was 17 months. The median diagnostic delay was 13.75 months. Patients with residual AC activity in fibroblasts at more than 5.1% of the normal level survived significantly longer than patients with residual AC activity below this threshold. In addition, higher residual AC activity was associated with a later onset of symptoms.ConclusionFarber disease onset is in infancy. Diagnostic delay is typically substantial. Our data suggest a phenotype-biomarker association with implications for future clinical and therapeutic trials. In the absence of a prospective multicenter natural-history study protocol, we believe that our modeling approach, based on published case descriptions, is the best and most timely approximation for generalizability.